Floristic composition and stand characteristics of logged-over forest in sungai Asap, Belaga - Doulos Nalau, Bujang (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The Malaysian Palm Oil Board (MPOB) Research Station at Sungai Asap, Belaga, Sarawak is located approximately 100 km from Bintulu town. The 120 hectares of logged-over forest is administered by MPOB as a conservation area and designated as a model for oil palm plantation. It involves the integration of oil palm plantation and forested area. The logged-over forest had been selectively logged by logging company between 10 to 15 years before MPOB came in 200~ A study was conducted to determine the floristic and stand structure of logged-over forest in Sungai Asap for conservation purpose. Specifically the objectives of this study were to determine the tree species composition, diversity and forest stand structure of logged-over forest in Sg. Asap. A total of 22 sampling plots of 20 x 20 m were established within two biodiversity strips which have been established by MPOB. The plots were enumerated for tree species composition, stand density, diameter size distribution and vertical vegetation layers. A total of 1075 trees above 5 cm diameter at breast height (dbh) were enumerated which consisted of 45 families and 187 species. The most dominant species as indicated by their important value index (lVI) was Macaranga triloba (6:92%). The other two dominant species were Shorea parvifolia (3.97%) and Shorea sp. (3.94%). The number of tree per ha or tree density was 1222 and total tree height had an average of 10.97 m. The mean diameter at breast height and basal area were 13.85 cm and 29.39 m2ha-1 , respectively. Emergent tree was represented by a single species, Shorea parvifolia which recorded at 38 m. Dipterocarpaceae family dominated all structure characteristics of logged-over forest showed good regeneration indicated by high population of medium-sized individuals in term of tree height.